2013
DOI: 10.1111/aos.12302
|View full text |Cite
|
Sign up to set email alerts
|

Visual performance and ocular abnormalities in deaf children and young adults: a literature review

Abstract: ABSTRACT.Visual defects are common in deaf individuals. Refractive error and ocular motor abnormalities are frequently reported, with hyperopia, myopia, astigmatism and anomalies of binocular vision, all showing a greater prevalence in deaf individuals compared with the general population. Near visual function in deaf individuals has been relatively neglected in the literature to date. Comparisons between studies are problematic due to differences in methodology and population characteristics. Any untreated vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
1
12
2
4
Order By: Relevance
“…Evidence suggests that the left MFG is the specific brain region for Chinese reading [ 32 ], and the left IFG is extremely important for language comprehension and production [ 33 ]. The decreased connectivity might be caused by the inferior skills of reading or speaking observed in most of the deaf subjects [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the left MFG is the specific brain region for Chinese reading [ 32 ], and the left IFG is extremely important for language comprehension and production [ 33 ]. The decreased connectivity might be caused by the inferior skills of reading or speaking observed in most of the deaf subjects [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The auditory cortex in deaf subjects can be activated by various tasks, such as speech ( Macsweeney et al., 2001 , 2002 ; Nishimura et al, 1999 ; Yoshida et al, 2011 ) and visual stimuli ( Fine et al, 2005 ; Finney et al, 2001 , 2003 ; Karns et al, 2012 ), which is a phenomenon known as “cross-modal plasticity”. Additionally, brain regions involved in language and visual functions change in deaf subjects as demonstrated by many studies ( Macsweeney et al, 2009 ; Li et al, 2012 ), which is suggested to be caused by the use of sign language as well as the lower level of reading or speaking skills observable in deaf youngsters ( Hollingsworth et al, 2014 , for review; Parasnis et al, 2003 ; Pavani and Bottari, 2012 ; Quittner et al., 2004 ). Therefore, it is interesting to investigate the alterations of brain regions involved in auditory, language and visual processing in prelingually deaf adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4 Furthermore, many deaf individuals have other types of undiagnosed or inadequately corrected visual disturbances. 2 Inadequate recognition and treatment of vision problems may exacerbate the challenges that deaf individuals already face in seeking healthcare services, which can include communication barriers, physician distrust, and inadequate insurance coverage.…”
Section: Discussionmentioning
confidence: 99%
“…However, as previously stated, multiple studies have shown that deaf individuals have higher rates of refractive error than hearing individuals. 1,4,7 Accordingly, any chart that aims to serve deaf individuals should also be suitable for use during manifest refraction. The Handy Eye Chart is well suited for manifest refraction, because the patients can use one hand to mimic the optotype while maintaining fixation on the chart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation